2013
DOI: 10.1080/17458080.2013.824617
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activities of sonochemically prepared Au-core/Pd-shell-structured bimetallic nanoparticles immobilised on TiO2and its dependence on Pd-shell thickness

Abstract: Catalytic activities of sonochemically prepared Au-core/Pd-shell-structured bimetallic nanoparticles (NPs) immobilised on TiO 2 were evaluated. Comparing with the mixture of monometallic Au and Pd NPs on TiO 2 , core/shell-immobilised catalysts exhibited higher activities for the partial reduction of nitrobenzene (NB) to aniline (AN), suggesting that the synergistic effect originating from the core/ shell structure enhanced the catalytic activities. In the case of high Au/Pd ratios, where the Pd-shell thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The synthesis of bimetallic AuPd nanoparticles is known to be complex with the composition oen varying depending on the metal particle size when both metals are introduced simultaneously. 51,52 There are numerous groups who have reported preparation methods that produce nanoparticles with gold cores and palladium shells, [56][57][58][59]64 however, these oen form in addition to monometallic particles and bimetallic particles where the two metals are mixed/alloyed. In this work, the synthesis method reported by Wilson et al 64 was adopted, which appeared to produce core-shell nanoparticles based on the characterisation presented.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of bimetallic AuPd nanoparticles is known to be complex with the composition oen varying depending on the metal particle size when both metals are introduced simultaneously. 51,52 There are numerous groups who have reported preparation methods that produce nanoparticles with gold cores and palladium shells, [56][57][58][59]64 however, these oen form in addition to monometallic particles and bimetallic particles where the two metals are mixed/alloyed. In this work, the synthesis method reported by Wilson et al 64 was adopted, which appeared to produce core-shell nanoparticles based on the characterisation presented.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
“…In principle, when the shell is relatively thin, the electronic properties of the shell metal may be perturbed, which offers exciting possibilities with regards to adsorption and catalytic behaviour. [56][57][58] In-spite of the obvious appeal, synthesis methods rarely seem to produce only core-shell nanoparticles. Instead, a mixture of coreshell, bimetallic and monometallic particles are oen formed, making evaluation of the catalytic properties of individual species challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of Au/Pd core-shell NPs using ultrasound irradiation has also been reported. [16][17][18][19][20][21][22] Nitani et al reported that Au/Pd core-shell NPs with an average particle size of 8.3 nm were synthesized from HAuCl 4 and Na 2 PdCl 4 using ultrasound irradiation. 16) The particle size and deposition characteristics of NPs are known to depend on the concentration of Au and Pd ions.…”
mentioning
confidence: 99%
“…Mizukoshi et al reported that Au/ Pd core-shell NPs synthesized with a high Pd content tend to be relatively smaller and exhibit finer dispersion than those with a high Au content. 17) Despite these advances, the deposition of Au/Pd core-shell NPs on cathode materials to decrease charge transfer resistance has not been studied yet. With this aim, we study in this paper the synthesis and deposition of Au/Pd NPs having a core-shell structure on the surface of LFP/C using ultrasound irradiation.…”
mentioning
confidence: 99%